2011
DOI: 10.1007/s00432-011-1026-9
|View full text |Cite
|
Sign up to set email alerts
|

Interventional therapies of unresectable liver metastases

Abstract: Liver metastases are the major cause of mortality in patients with gastrointestinal carcinomas and other malignant tumors, carrying a poor prognosis and presenting considerable management. Surgical resection remains the only curative therapy for liver metastases up to now. However, only a small percentage of patients are suitable for curative resection due to many factors: multi-centric tumors, extrahepatic metastases, early vascular invasion, and coexisting advanced liver cirrhosis. In non-surgical cases, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The safety and effectiveness of cryoablation for the treatment of malignant tumors have been demonstrated by various animal experiments and clinical trials. 19 The successful local control of hepatocellular carcinoma and liver metastases from other primary tumors (eg, breast cancer) has demonstrated the effectiveness of this safe and reliable technique. 20,21 A study by Zhang et al 22 demonstrated the safety and effectiveness of hepatic cryoablation for the treatment of liver metastases from breast cancer and resulted in the improved quality of patients' life with unresectable cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and effectiveness of cryoablation for the treatment of malignant tumors have been demonstrated by various animal experiments and clinical trials. 19 The successful local control of hepatocellular carcinoma and liver metastases from other primary tumors (eg, breast cancer) has demonstrated the effectiveness of this safe and reliable technique. 20,21 A study by Zhang et al 22 demonstrated the safety and effectiveness of hepatic cryoablation for the treatment of liver metastases from breast cancer and resulted in the improved quality of patients' life with unresectable cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It is a combination of fatigue, abdominal pain, nausea, vomiting, anorexia, fever, and cachexia. This is an early transient complication that is not evident radiologically (Qian 2011 ). tmargarida@gmail.com radiological manifestations.…”
Section: Hepatic Complications Due To Transarterial Chemoembolizationmentioning
confidence: 95%
“…In this procedure the arterial blood supply of the lesion is embolized in order to induce necrosis and a chemotherapeutic agent is administered selectively to the lesion (Qian 2011 ). In the conventional procedure a mixture of a cytotoxic drug emulsifi ed with ethiodized oil (known as Lipiodol or Ethiodol), which is radiopaque, is injected into the arterial branch supplying the lesion.…”
Section: Hepatic Complications Due To Transarterial Chemoembolizationmentioning
confidence: 99%
See 2 more Smart Citations